Предмет: Математика,
автор: danilzvonenko3
(3x-1)(3x+1)=(2x+1)²+x-1
Ответы
Автор ответа:
1
Пошаговое объяснение:
(3x-1)(3x+1)=(2x+1)^2+x-1
9x^2-1=4x^2+4x+1+x-1
9x^2-4x^2-4x-x=1
5x^2-5x-1=0
D=b^2-4ac=(-5)^2-4×5×(-1)=25+20=45
X1=(-b+кореньD)/2a=
=(5+корень45)/2×5=
=(5+корень(9×5))/10=
=(5+3корень5)/10
Х2=(5-3корень5)/10
Ответ :
Х1=(5+3корень5)/10
Х2=(5-3корень5) /10
Похожие вопросы
Предмет: Окружающий мир,
автор: AgafonovaMilana
Предмет: Английский язык,
автор: Сосисочка2004
Предмет: Русский язык,
автор: Lisenok730
Предмет: Русский язык,
автор: viki157
Предмет: Математика,
автор: arinayakov0206